Regulating Tumor N6‐Methyladenosine Methylation Landscape using Hypoxia‐Modulating OsSx Nanoparticles. Issue 1 (7th December 2020) - Zheng, Yue; Ling, Yuyi; Zhang, Dong‐Yang; Tan, Cai‐Ping; Zhang, Hang; Yang, Gang‐Gang; Wang, Hongsheng; Ji, Liang‐Nian; Mao, Zong‐Wan
Abstract: The epigenetic dysregulation and hypoxia are two important factors that drive tumor malignancy, and N 6 ‐methyladenosine (m 6 A) in mRNA is involved in the regulation of gene expression. Herein, a nanocatalyst OsS x ‐PEG (PEG = poly(ethylene glycol)) nanoparticles (NPs) as O2 modulator is developed to improve tumor hypoxia. OsS x ‐PEG NPs can significantly downregulate genes involved in hypoxia pathway. Interestingly, OsS x ‐PEG NPs elevate RNA m 6 A methylation levels to cause the m 6 A‐dependent mRNA degradation of the hypoxia‐related genes. Moreover, OsS x ‐PEG NPs can regulate the expression of RNA m 6 A methyltransferases and demethylases. Finally, DOX@OsS x ‐PEG (DOX = doxorubicin; utilized as a model drug) NPs modulate tumor hypoxia and regulate mRNA m 6 A methylation of hypoxia‐related genes in vivo. As the first report about relationship between catalytic nanomaterials and RNA modifications, the research opens a new avenue for unveiling the underlying action mechanisms of hypoxia‐modulating nanomaterials and shows potential of regulating RNA modification to overcome chemoresistance. Abstract : Modified OsS x catalytic nanoparticles (NPs) are developed as drug carriers for combined chemo‐photothermal therapy with multi‐model imaging. OsS x ‐PEG NPs can catalyze decomposition of H2 O2 to produce O2 to modulate hypoxia and enhance drug sensitivity. Moreover, OsS x ‐PEG NPs can cause mRNA degradation of hypoxia‐related genes by regulating RNA m 6 A methylation levels.